Biomass‐based materials for advanced supercapacitor: principles, progress, and perspectives - Yaxuan Wang; Ting Xu; Kun Liu; Meng Zhang; Xu‐Min Cai; Chuanling Si (Aggregate, 2024)
Abstract Supercapacitors exhibit considerable potential as energy storage devices due to their high power density, fast charging and discharging abilities, long cycle life, and eco‐friendliness. With the increasing environmental concerns associated with synthetic compounds, the use of environment friendly biopolymers to replace conventional petroleum‐based materials has been widely studied. Biomass‐based materials are biodegradable, renewable, environment friendly and non‐toxic. The unique hierarchical nanostructure, excellent mechanical properties and hydrophilicity allow them to be used to create functional conductive materials with precisely controlled structures and different properties. In this review, the latest development of biomass‐based supercapacitor materials is reviewed and discussed. This paper describes the physical and chemical properties of various biopolymers and their impact on supercapacitors, as well as the classification and basic principles of supercapacitors. Then, a comprehensive discussion is presented on the utilization of biomass‐based materials in supercapacitors and their recent applications across a range of supercapacitor devices. Finally, an overview of the future prospects and challenges pertaining to the utilization of biomass‐based materials in supercapacitors is provided.